Impact of dietary patterns on body weight in girls with central precocious puberty treated with leuprolide during the COVID-19 pandemic - Figueiredo, Fabiana Neves; Ganen, Aline de Piano; Figueiredo, Carolina Costa; Evangelista, Nara Michelle de Araújo; Fernandes, Vânia de Fátima Tonetto; Pacheco, Luciana de Aguiar; Kato, Tatiana; Colares Neto, Guido de Paula (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the nutritional status and dietary patterns of girls with central precocious puberty (CPP) undergoing treatment with leuprolide acetate during the COVID-19 pandemic.MethodsA cross-sectional study was conducted with 59 girls, aged 5–13 years, diagnosed with CPP and treated with leuprolide acetate. Between May and December 2021, a food frequency questionnaire (FFQ) and a 24-hour dietary recall (24-h DR) were administered. The Fornés score was used to quantify consumption markers of healthy (beans, fruits, vegetables, and greens) and unhealthy (hamburgers, sugar-sweetened beverages, ultra-processed foods, and sweets) foods. Higher scores reflected greater intake of the respective food groups.ResultsOf the participants, 31 (52.5%) showed a reduction in their BMI Z-score (mean change: −0.32 ± 0.26), while 28 (47.5%) had an increase (mean change: 0.25 ± 0.22). Girls who reduced their BMI Z-score had significantly higher Fornés scores for healthy food markers (p = 0.02), particularly for fresh fruits (p = 0.04) and greens and vegetables (p = 0.01). A negative correlation was found between BMI Z-score variation and the Fornés score for healthy food markers (p = 0.02), including fruits (p = 0.02) and greens and vegetables (p = 0.02). No significant associations were observed between BMI Z-score variation and age at treatment onset (p = 0.22) or treatment duration (p = 0.43).ConclusionIn girls with CPP treated with leuprolide acetate, greater consumption of healthy foods—especially fruits and vegetables—was associated with decreased BMI Z-scores. These findings underscore the role of dietary quality in energy balance and support nutritional monitoring during GnRHa therapy, particularly under lifestyle-altering conditions such as the COVID-19 pandemic.